Analysis of Maxillofacial Fractures Based on the Etiology in Southeast China: A 10-Year, Multi-Center Study. Issue 4 (8th June 2021) - Huang, Li; Jiang, Canyang; Lin, Yuerong; Wen, Yuejin; Huang, Xuelei; Huang, Jianping; Lin, Lisong
Abstract : Supplemental Digital Content is available in the text Abstract : Background: The aim of this study was to explore the characteristics and correlation of maxillofacial fractures and concurrent injuries with different injury causes. Methods: In this retrospective study, data were collected from patients treated for maxillofacial fractures in 3 oral and maxillofacial surgery departments in Southeast China, from January 2010 to December 2019. The information was obtained from clinical notes and surgical records using a standardized data collection form, and some causes of injuries were confirmed by telephone follow-ups and police records. These patients were divided into 7 groups according to the etiology: bicycle accident, electric bicycle accident, motorcycle accident, automobile accident, fall at ground level, fall from a height, and assault-related accident. Statistical tests were performed using R software (version 3.1.1), and all P -values were computed based on Chi-square tests and set at 0.05. Results: During this 10-year retrospective study, a total of 1772 patients with definite causes were analyzed. The average age was approximately 35.04 years (9 months–94 years). All patients were treated with open reduction and rigidly internal fixation, and the average duration was approximately 6.51 days (range 0 day–50 days), that from the time of the injury to the time of treatment. Traffic accidents were identified as the main cause of maxillofacial fracture (57.62%; n = 1021 of 1772 cases). In different etiology groups, there were statistically significant differences in the distribution of age, sex, maxillofacial fracture type, and concurrent injuries (all P < 0.001). However, the main cause of maxillofacial injuries was falls (fall at ground level and fall from a height) in children, and the highest incidence of the cause of maxillofacial injuries was bicycle accident in adolescents. Compared with the other groups, zygomatic complex fracture was more common in the electric bicycle accident group, panfacial fracture was more common in the automobile accident group, and mandible fracture was more common in the other groups. Conclusion: The results of this study suggest that patients with maxillofacial fractures caused by different injuries had their own unique characteristics. These findings may assist us in avoiding misdiagnosis and treatment delays, and may make treatment plans faster.